Perceptions of 5th and 6th Grade Elementary Students Upon Cooperation in the Physical Education Lesson After their Educators’ Training - Papamichou, Ασπασία; Derri, Βασιλική; Vernadakis, Νικόλαος (Inquiries in Physical Education and Sport, 2018)
The constructive learning strategies in Physical Education (PΕ) include the cooperation of students, which can make the lesson of PΕ a means of social coexistence and equality promotion. The aim of the present study was to identify possible differences in the perceptions of fifth and sixth grade elementary students in terms of their cooperation in the physical education lesson, after their teachers’ training. Distance training lasted eight weeks. Three hundred one 5th and 6th grade elementary students from all over Greece participated in the study. They were divided into two groups; an experimental (n=160) and a control group (n=141). The experimental group included students whose teachers’ voluntarily attended the distance training program. For the assessment of pupils’ perceptions, the Constructivist Teaching Practices Inventory in Elementary Physical Education (CTPI-EPE) (Chen, Burry-Stock, & Rovegno, 2000) was adapted. Analysis of variance with repeated measurements was applied. The results showed a statistically significant difference in the perceptions of the pupils in the experimental group regarding the facilitation of their cooperation, after their teachers’ training, higher than that in the control group. In conclusion, it appears that the Physical Educator Teachers (PETs) training program enhanced student cooperation in the physical education lesson.